Discrimination between Inflammatory and Fibrotic Activity in Crohn's Disease-Associated Ileal-Colonic Anastomotic Strictures by Combined Ga-68-FAPI-46 and F-18-FDG-PET/CT Imaging - Beck, Michael; Kuwert, Torsten; Atzinger, Armin; Gerner, Maximilian; Hartmann, Arndt; Saake, Marc; Uder, Michael; Neurath, Markus; Atreya, Raja (Visceral Medicine, 2024)
Introduction: The development of an intestinal stricture in patients with Crohn s disease represents an important and frequent complication, reflecting the progressive nature of the disease. Depending on the inflammatory and fibrotic composition of the stricture, intensified medical therapy, interventional endoscopy, or surgical intervention is required. However, currently available diagnostic approaches can only assess the level of inflammation, but not the degree of fibrosis, limiting rational therapeutic management of Crohn s disease patients. Recently, prolyl endopeptidase fibroblast activating protein (FAP) has been functionally implicated in fibrotic tissue remodelling, indicating it as a promising target for detection of sites of fibrotic tissue remodelling. Thus, intestinal fibrosis might be visualized using Gallium-68 labelled inhibitors of FAP (FAPI). While F-18-fluorodeoxyglucose (FDG)-positron emission tomography (PET)/CT is a standard diagnostic tool for visualizing inflammatory processes, we combined Ga- 68-FAPI-46-PET/CT and F-18-FDG-PET/CT to differentiate predominantly fibrotic or inflammatory areas in Crohn s disease patients with ileo-colonic strictures. Methods: In our study, we analysed three Crohn s disease patients with anastomotic ileo-colonic strictures who underwent both dynamic Ga-68-FAPI-46-PET/CT and static F-18-FDG-PET/CT imaging to assess the level of visualized fibrotic areas within the stricture and differentiate it from inflammatory ones. PET images were analysed both visually and quantitatively. Furthermore, conventional MR enterography and endoscopy were performed in parallel to correlate observed findings. Two of the included patients underwent surgery and the histological specimen were analysed for the level of inflammation and fibrosis, which results were similarly compared to the findings of the PET imaging procedures. Results: Different uptake patterns of Ga-68- FAPI-46 could be observed in the anastomotic ileo-colonic strictures of the examined Crohn s disease patients, respectively. Immunohistochemical analyses demonstrated that there was a correlation between the level of Ga-68- FAPI-46 uptake and severity of fibrosis, while FDG uptake correlated with the inflammatory activity in the analysed strictures. Discussion: The combination with F-18-FDGPET/CT represents a promising imaging modality to distinguish inflammation from fibrosis and guide subsequent therapy in stricturing Crohn s disease patients, warranting further studies.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Crohn s disease; FAPI-PET/CT; Fibrosis; Ga-68-FAPI-46; Strictures